Regional Economic Outlook, October 2011. - Dept, International Monetary Fund. Asia and Pacific (Regional Economic Outlook., 2011)
In line with the weaker global outlook, growth in Asia is expected to be slightly lower in 2011-12 than forecast in April 2011, mainly as a result of weakening external demand, but the expansion should remain healthy, supported by domestic demand, which has been generally resilient. Overheating pressures remain elevated in a number of economies, with credit growth still robust and inflation momentum generally high, though inflation is expected to recede modestly after peaking in 2011. The sell-off in Asian financial markets in August and September 2011 underscores that an escalation of euro ar.